A Strategic Planning Intervention Employing Large Group Change: A Scholar/Practitioner Application - Coleman, Tanjia M.; Sorensen, Peter; Yaeger, Therese F.; Hinrichs, Gina (Journal of Management Policy and Practice, 2017)
We present a scholar-practitioner collaboration applying a large group positive change project, representing the first such application methodology involving first responders. Positive change intervention is based on a multistage process involving Appreciative Inquiry and S.O.A.R. (Strengths, Opportunities, Aspirations and Results), designed to engage the community in inclusion, transparency, and mutual commitment in developing a strategic plan. Part of this plans objective is acquiring national accreditation, which has only been obtained by 217 of 30,052 fire department in the country. The project included 30 interns and 64 interviews with employees, trustees, and community residents, in preparation for the SOAR strategic planning session